Constructing Motherhood Identity Against Political Violence
XX, 181 p.
Keywords: This volume offers a nuanced understanding of female agency in political violence by reviewing and analyzing the political construction of motherhood as a form of social agency against political violence committed by both state and non-state actors in different parts of the world. While the international relations discipline has traditionally viewed the relationship between women and violent actors as an exploitative one, this book demonstrates that taking maternal bodies seriously creates important intellectual space to examine the types and kinds of violence the discipline of IR takes seriously and the types and kinds of resistance practiced by mothers but often overlooked (at least by male/mainstream IR). Focusing on motherhood as an agency of change, this volume will appeal to scholars in the field of gender and international security, think tanks working on political and security affairs, social activists, policymakers, an interested public audience, as well as undergraduate and postgraduate students undertaking study or research associated with gender and political violence.